THE FEASIBILITY OF IMPLEMENTING “BUDDY PROGRAM” BETWEEN LOCAL BALINESE STUDENTS AND INCOMING STUDENTS FROM OUTSIDE OF BALI IN UNIVERSITAS DHYANA PURA - Luh Ayu Puspita Dewi; Putu Chrisma Dewi; Ni Luh Christine P. S. Suyasa (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2020)
ABSTRACTBuddy Program is a program that pairs between local student groups and migrantstudent groups. In this case, the buddy program meant by the Universitas Dhyana Pura isslightly different, between local students and students who come from outside the island ofBali, but still from Indonesia. This study discusses about preliminary interest among localUniversitas Dhyana Pura students in Buddy Program and find out whether the buddy programcan be applied or not in Universitas Dyhana Pura. The method used in this project isquantitative descriptive. Data obtained from a sample of the study population were analyzedaccording to the statistical methods used and then interpreted.Keywords: buddy program, Universitas Dhyana Pura, local Balinese student